FABRICATION OF SANSEVIERIA TRIFASCIATA FIBER REINFORCED POLYLACTIC ACID (PLA) COMPOSITE FILAMENT: OPTIMIZATION OF FORMABILITY - Ariella Eko Putra, Dhani
Implants must be made from materials that are biocompatible and biodegradable and can be custom manufactured at low production costs. Polylactic Acid (PLA) has a low processing temperature and is biodegradable but its mechanical properties are lower than human bone. The addition of Sansevieria trifasciata (STF) fiber has the potential to be a reinforcement because it has the appropriate mechanical properties and is biodegradable. Fused Deposition Modelling (FDM) is commonly used because it is easy, inexpensive and produces highly customizable products. FDM process requires a material in the form of a filament with a continuous length and a diameter of 1,75 ± 0,1 mm. Filament formability will be influenced by fiber length, water content, fiber surface treatment, extrusion temperature, screw speed and drawing speed during extrusion. In this research, the initial zone temperature and drawing speed parameters were examined for their influence on the formability and mechanical properties of 2 wt% STF reinforced PLA composite filament. STF reinforced PLA composite filaments were characterized using MFR, FTIR and XRD to determine the effect of initial zone temperature on filament formability as well as materialography, tensile test and SEM to determine the effect of drawing speed on the formability and mechanical properties of filaments. STF reinforced PLA composite filament was successfully produced with a continuous length and diameter of 1,79 ± 0,07 mm using initial zone temperature parameters of 133°C and a drawing speed of 10,8 rpm.